Carbon Redistribution During the Stages of Generation and Destruction of Municipal Solid Waste Organic Component - Prykhodko, Veronika; Safranov, Tamerlan; Shanina, Tatyana; Illyash, Oksana (International Journal of Engineering and Technology, 2018)
The estimation of carbon redistribution during generation and decomposition of organic component of municipal solid waste for different ways of treatment is presented in paper. The study of the transformation and distribution of carbon compounds during treatment options of organic component of municipal solid waste is implemented on the example of Odessa region and Odessa in particular. Such options as disposal and complex recovery of organic wastes are consideredÂ Â